Urinary sodium-to-potassium ratio: a simple and useful indicator of diet quality in population-based studies - Parvin Mirmiran; Zahra Gaeini; Zahra Bahadoran; Asghar Ghasemi; Reza Norouzirad; Maryam Tohidi; Fereidoun Azizi (European Journal of Medical Research, 2021)
Abstract Background Current evidence regarding the prognostic relevance of urinary sodium-to-potassium ratio (Na-to-K ratio), as an indicator of diet quality is limited. This study was conducted to investigate whether urinary Na-to-K ratio could be related to habitual dietary patterns, in a general population. Methods This study was conducted in the framework of the Tehran Lipid and Glucose Study (2014–2017) on 1864 adult men and women. Urinary Na and K concentrations were measured in the morning spot urine samples. Dietary intakes of the participants were assessed using a validated 147-item Food Frequency Questionnaire (FFQ) and major dietary patterns were obtained using principal component analysis. Mediterranean dietary pattern and Dietary Approaches to Stop Hypertension (DASH) score, were also calculated. Multivariable-adjusted linear regression was used to indicate association of dietary patterns and urinary Na-to-K ratio. Results Mean (± SD) age of participants was 43.7 ± 13.9 years and 47% were men. Mean (± SD) urinary Na, K and the ratio was 139 ± 41.0 and 57.9 ± 18.6 mmol/L, 2.40 ± 0.07, respectively. Higher urinary Na-to-K ratio (> 2.37 vs. < 1.49) was related to lower intakes of vegetables (282 vs. 321 g/day), low-fat dairy (228 vs. 260 g/day) and fruits (440 vs. 370 g/day). Western dietary pattern was related to higher urinary Na-to-K ratio (β = 0.06; 95% CI 0.01, 0.16). Traditional dietary pattern, Mediterranean and DASH diet scores were inversely associated with urinary Na-to-K ratio (β = − 0.14; 95% CI − 0.24, − 0.11, β = − 0.07; 95% CI − 0.09, − 0.01, β = − 0.12; 95% CI − 0.05, − 0.02, respectively). Conclusions Spot urinary Na-to-K ratio may be used as a simple and inexpensive method to monitor diet quality in population-based epidemiological studies.